Improving Forest Fire Mitigation in Indonesia: A Lesson from Canada - M. Bayu Rizky Prayoga; Raldi Hendro Koestoer (Jurnal Wilayah dan Lingkungan, 2021)
Forest fire is a hydrometeorological disaster that routinely occurs in Indonesia every dry season and often hits areas with extensive peatland cover. The lack of scientific references explaining peatlands' physical parameters and their relationship to hotspots' occurrence also contributes to the government intervention's ineffectiveness in forest fires suppression because they are mainly executed in severe drought conditions. Strengthening mitigation, especially at the preparedness stage, is needed to detect forest fires earlier, prevent not from spreading widely, and not cause many environmental, social, and economic losses. This study aims to explain the gaps in forest fire disaster management in Indonesia, which have not maximized the results of observations from physical land and weather conditions as a basis for making decisions for more preventive forest fire mitigation. This study’s analysis is conducted using literature studies method from several reports, scientific articles, and regulations related to forest fires. This study’s analysis results explain how physical land monitoring and observation can provide a scientific basis that can be used as input in formulating policies, especially regarding the determination of disaster status on forest fire phenomena. Furthermore, this study explains how a paradigm shift in forest fire disaster management is needed in Indonesia through a more preventive approach to implement forest fire disaster mitigation can be more effective and efficient.